Epidermal Growth Factor Receptor immunohistochemical expression in hepatocellular carcinoma without Epidermal Growth Factor Receptor exons 18-21 mutations - Nikolova, Dafina; Trajkovska, Meri; Trpcevska Nikolovska, Emilija; Eftimov, Aleksandar; Jovanovikj, Rubens; Janevska, Vesna (Walter de Gruyter GmbH, 2022)
Introduction: EGFR targeted therapies, have been proved beneficial for patients with HCC, nevertheless additional research on EGFR immunoexpresion and EGFR mutations is still needed, especially in population in which it has not been done yet. The aim of this study is to evaluate EGFR immunoexpression in HCC without EGFR exons 18-21 mutations and to evaluate its influence on survival in HCC patients in North Macedonia. Methods: We studied 31 cases of HCC for EGFR immunohistochemical expression and EGFR exons 18-21 mutations. The following clinical parameters were analyzed: Hepatitis B and C virus infection, presence of cirrhosis, tumor size, enlarged lymph nodes, metastases, alpha fetoprotein level and overall survival. Presence of the EGFR immunosignal (membranous and cytoplasmic) and the percentage of positive tumor cells in the entire tumor tissue specimen were semi-quantitatively determined. Results: Hepatitis B and C virus infection, tumor size, metastatic disease and EGFR immunoexpression have influence on patient's survival. No EGFR exons 18-21 mutations were detected in this group of HCCs. EGFR expression of 61%-80% in tumor tissue significantly influenced survival of the patients (p < 0.01). Multiple Cox regression confirmed tumor size of 5-10 cm (p < 0.05), tumor size > 10 cm (p < 0.01) and EGFR expression in range of 61% to 80% (p < 0.05) as independent survival predictors in patients with HCC. Conclusion: EGFR overexpression in range of 61% to 80% was an independent survival predictor in patients with HCC, implying that these patients could benefit from EGFR inhibition. However, the absence of EGFR mutations in exons 18-21 in any of the cases of this study suggest that single drug EGFR targeted therapy in patients with HCC may be insufficient.
Keywords: Epidermal Growth Factor Receptor; exon 18–21; gene mutation; hepatitis B virus infection; hepatocellular carcinoma; survival; immunohistochemistry